Logos – in die Seele geschrieben (Zu Platons Schriftkritik im Phaidros) - Simon, Attila (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
In Plato’s Phaedrus, in the context of the ‘critique of writing’ the phrase ‘writing in the soul’ occurs twice (276a5, 278A3). Why did Plato use this metaphor, with positive connotation, in a context which criticises ’writing’ in everyday sense? On the basis of the Phaedrus, I argue that the content of logos inscribed in the soul is not a philosophical doctrine, formulated in propositions, but the continuous practice of dialectic as the philosophical way of life. On the basis of the broader context of 5th and 4th century literary texts, I argue that Plato uses this metaphor as a cliché which emphasizes the importance of the content that should be inscribed in the soul for remembrance, even though the phrase is somewhat at odds with the narrower context.